Long-lasting control of Anopheles arabiensis by a single spray application of micro-encapsulated pirimiphos-methyl (Actellic® 300 CS) - Oxborough, Richard M (BioMed Central, 2014)
BACKGROUND: Pyrethroid-resistant mosquitoes are an increasing threat to malaria vector control. The Global Plan for Insecticide Resistance Management (GPIRM) recommends rotation of non-pyrethroid insecticides for indoor residual spraying (IRS). The options from other classes are limited. The carbamate bendiocarb and the organophosphate pirimiphos-methyl (p-methyl) emulsifiable concentrate (EC) have a short residual duration of action, resulting in increased costs due to multiple spray cycles, and user fatigue. Encapsulation (CS) technology was used to extend the residual performance of p-methyl. METHODS: Two novel p-methyl CS formulations were evaluated alongside the existing EC in laboratory bioassays and experimental hut trials in Tanzania between 2008-2010. Bioassays were carried out monthly on sprayed substrates of mud, concrete, plywood, and palm thatch to assess residual activity. Experimental huts were used to assess efficacy against wild free-flying Anopheles arabiensis, in terms of insecticide-induced mortality and blood-feeding inhibition. RESULTS: In laboratory bioassays of An. arabiensis and Culex quinquefasciatus both CS formulations produced high rates of mortality for significantly longer than the EC formulation on all substrates. On mud, the best performing CS killed >80% of An. arabiensis for five months and >50% for eight months, compared with one and two months, respectively, for the EC. In monthly bioassays of experimental hut walls the EC was ineffective shortly after spraying, while the best CS formulation killed more than 80% of An. arabiensis for five months on mud, and seven months on concrete. In experimental huts both CS and EC formulations killed high proportions of free-flying wild An. arabiensis for up to 12 months after spraying. There was no significant difference between treatments. All treatments provided considerable personal protection, with blood-feeding inhibition ranging from 9-49% over time. CONCLUSIONS: The long residual performance of p-methyl CS was consistent in bioassays and experimental huts. The CS outperformed the EC in laboratory and hut bioassays but the EC longevity in huts was unexpected. Long-lasting p-methyl CS formulations should be more effective than both p-methyl EC and bendiocarb considering a single spray could be sufficient for annual malaria control. IRS with p-methyl 300 CS is a timely addition to the limited portfolio of long-lasting residual insecticides.